A formação inicial de professores e a cultura científica na educação básica: problematizando a prática docente na interface das disciplinas estágio supervisionado e história da física - Portela, Sebastiao Ivaldo Carneiro [UNESP] (2014)
In this work, developed with a group of undergraduates, we have promoted some reflections and proposed some actinos concerning the scientific culture construction in secondary school, based on the initial formation influences of science understanding, the challenges faced in the school context and the process of preparation, construction and aplication of problem-solving-historical texts in schools. The experiment was performed in 2011, in a created space on the Supervised Practicum and the History of Physics disciplines interface; it involved a group of undergraduates from Unesp Engeneering College of Ilha Solteira - São Paulo, Brazil. This participated research has the purpose of analysing the process in which te undergraduates have lived, from the point of view of conditioning element manifestation of their practices, aiming, thereby, to expand the knowledge that justifiy the origin of the difficulties of the emancipation for transmitting Physics knowledge in schools environment. The collected data were drawn from the transcripts of discussions during the Supervised Practicum and the History of Physics classes, two semi-structured interviews and reports of the classes taught by the undergraduates in secondary schools. The analysis of the data contents points to the need of considering, in the professional prepartation of teachers, factors that influence their practices as cultural heritage of Physics teaching, the systemic forces, the specific knowledge of Physics teaching and the socio-organizational factors in the school context